Cost-Benefit Analysis of Genotype-Guided Interruption Days in Warfarin Pre-Procedural Management - Islam, Eljilany (2022)
Warfarin is commonly used in thromboembolic conditions. Warfarin interruption represents a significant challenge in pre-operative warfarin management as it is associated with major consequences. Genetics polymorphism demonstrated to be a significant predictor of the required days of warfarin interruption. This study sought to assess the economic benefit of implementing a pharmacogenetic-guided approach in the preprocedural warfarin management. From the hospital's perspective, a cost-benefit analysis was conducted based on a 1-year decision-analytic follow-up model of the economic implications of using a pharmacogenetic algorithm vs standard of care in pre-operative warfarin management in the Hamad Medical Corporation, Qatar. The benefit of the interventional algorithm was based on estimated reduction in the probabilities of clinical events and their cost, added to the avoided cost because of canceled procedures. The cost of the algorithm was the cost of the genotyping assay. The model event probability inputs were extracted from major literature clinical trials, and the setting-specifc and cost inputs were locally obtained. The model was based on a multivariate analysis at its base case. As per 10.3% prevalence of genetic variants, 82% bridging, and a calculated 20% optimization in the preparative period of warfarin management, the benefit to cost ratio was 4.0 in favor genotype-guided approach. This positive benefit to cost ratio was maintained in 100% of the simulated study cases. Sensitivity analyses confirmed the robustness and generalizability of the study conclusion. A pharmacogenetic- guided pre-operative warfarin interruption management is a cost-beneficial approach in the Qatari practice.